ÌFẸ́-INÚ AND SOCIAL ORDER IN YORÙBÁ THOUGHT SYSTEM (2014)
Ìfẹ́-Inú, the human will in Yorùbá ontology, exercises considerable influence on social order, which is the harmonious functioning of different facets of society to enhance human flourishing and development. However, the persistence of social disorder has made sustenance of peace and development difficult in contemporary society due to lack of consideration for Ìfẹ́-Inú. Earlier studies on social order have emphasised the physical actions of the human person, either as individuals or collectives, as determinants of social order while under-exploring the state of Ìfẹ́-Inú, which produces, as well as drives decisions and actions in human persons. This study, therefore, philosophically examined Ìfẹ́-Inú and how it is mediated in Yorùbá thought to initiate decisions and actions, with a view to promoting a morally desirable social order that will guarantee peace and sustainable development. The study adopted Emile Durkheim’s methodological holism and Herbert Spencer’s methodological individualism as framework. Holism explains social order on the basis of an understanding of social institutions while individualism bases social order on individuals’ behaviours and conducts. Six relevant texts in the philosophy of the social sciences, five on ontology and six on Yoruba culture which deal extensively with the concept of the human person in relation to social order were purposively selected. The analytic, critical and reconstructive methods were employed in this study. The analytic method was used to elucidate the importance of the human will and social order. The critical method was employed to interrogate how social order is guaranteed through the mediation of Ìfẹ́-Inú in Yorùbá culture, while the reconstructive method was used to determine the constitution of ọmọlúwàbí (a virtuous person) through the mediation of Ìfẹ́-Inú. Texts in the philosophy of the social sciences established that human persons are determinants of social order, but did not consider Ìfẹ́-Inú in its ontological and moral dimensions as very significant in their explanations, and therefore, under-explored the connection between social order and the state of Ìfẹ́-Inú. Texts on ontology revealed the importance of Ìfẹ́-Inú as the initiator and driver of decisions and actions in human persons. Texts on Yorùbá culture revealed that Ìfẹ́-Inú is mediated by culture to ensure the formation of ọmọlúwàbí. Ọmọlúwàbí exhibits such virtues as trust, honesty, inter-dependence, integrity, cooperation and perseverance necessary for harmonious living. Critical reflections revealed that the mediation of Ìfẹ́-Inú ensures that citizens are socialised to become ọmọlúwàbí. At the normative level, ìwà (character) is central to the formation of ọmọlúwàbí and character development serves as the basis for taming the negative traits of Ìfẹ́-Inú. The mediation of Ìfẹ́-Inú by culture, to produce ọmọlúwàbí who will promote social order, addresses the role of Ìfẹ́-Inú in the areas of desires, actions and decisions which form the basis for the promotion of a morally desirable social order pursuant to the quest for peace and sustainable development in society. The mediation of Ìfẹ́-Inú in Yoruba culture which produces ọmọlúwàbí is capable of enhancing the promotion of a morally desirable social order. Therefore, Ìfẹ́-Inú is fundamental to peace and sustainable development in society.